A general strategy for high performance stretchable conductors based on carbon nanotubes and silver nanowires. Issue 33 (6th April 2017) - Cao, Lijun; Wang, Zhan; Liu, Yang; Shi, Rui; Wang, Xiangjing; Liu, Juqing
Abstract : A general strategy, combining prestraining and embedding, for high performance stretchable conductors based on one-dimensional conductive materials, has been proposed. Abstract : A general strategy for high performance stretchable conductors based on one-dimensional conductive materials is proposed. Our approach involves a combination of prestrain for high stretchability and embedding for electrical stability and smooth surface. The resulting stretchable conductors exhibit superior electrical stability with stretchability to 50% tensile strain and a 1000 cycle endurance test, demonstrating their potential as high performance conductors in stretchable electronics.